Study of protease activity of bacteria isolated from solid waste - Mainali, Smriti; Khadka, Nanu Maiya; Maharjan, Bijaya Laxmi; Lekhak, Binod (Scientific World, 2011)
Solid waste is one of the most visible environmental nuisances and major causes of pollution in the urban areas. But a considerable proportion of this waste is decomposable organic matter. The study was designed to study the activity of protease enzyme produced by proteolytic bacteria isolated from solid waste. Solid waste samples were collected from 20 different sites of Kathmandu valley and proteolytic bacteria were isolated by serial dilution and spread plate technique using gelatin incorporated agar media. Among 113 isolates 22 (3 being potent ones) were found to be proteolytic bacteria. Protease enzyme was extracted from the most potent ones by fermentation technology and purified by acetone precipitation method and ammonium sulphate fractionation. The enzyme from Micrococcus spp. was optimally active at 4°C and pH 8 while that from another isolate, which remained unidentified, was optimally active at 37°C and pH 9. The activity of 60% salt fraction of the enzymes from both the isolates was maximum. This indicates the possibility of implementation of these enzymes for the management of solid waste by decomposing the proteinous components of the waste. Key words: Solid waste; Enzyme activity; Proteolytic bacteria. DOI: http://dx.doi.org/10.3126/sw.v9i9.5527 SW 2011; 9(9): 93-96